Direct Instruction Approach to Abulution Practice Learning - Rizal Rahmatullah; Tatang Muh Natsir; Wilam Nafilah Robaeah (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2022)
With this mini research, it aims to determine the effectiveness of the learning processes through a direct instruction approach in learning materials for ablution practices at SDN 040 Pasawahan, Bandung City. The lesson plans made by the SDN 040 Pasawahan teacher have used a scientific approach including the process of observing, asking questions, gathering information, associating and communicating. The method used in this mini-research is to use a qualitative approach by exploring document studies with descriptive analysis methods that aim to provide a quick and accurate description of the effect of the direct instruction learning model in the practice of ablution at SDN 040 Pasawahan. Bandung. The results of a mini research study on the direct instruction approach in learning the practice of ablution at SDN 040 Pasawahan resulted in a learning process that was able to liven up the classroom atmosphere and was able to provide changes in the implementation of ablution procedures for students. Dengan adanya mini riset ini bertujuan untuk mengetahui kefektifan proses pembelajaran melalui pendekatan direct instruction dalam materi pembelajaran praktik wudhu pada SDN 040 Pasawahan Kota Bandung. RPP yang dibuat oleh guru SDN 040 Pasawahan sudah menggunakan pendekatan saintifik diantaranya memuat proses Mengamati, Menanya, Mengumpulkan Informasi, Mengasosiasi Dan Mengkomunikasikan. Adapun metode yang digunakan dalam penelitian mini riset ini adalah menggunakan jenis pendekatan kualitatif dengan mengeksplorasikan studi dokumen/teks (document studies) dengan metode analisis deskriptif yang bertujuan untuk memberikan gambaran secara cepat dan tepat tentang pengaruh model pembelajaran direct instruction dalam praktik wudhu di SDN 040 Pasawahan kota Bandung. Hasil penelitian mini riset tentang pendekatan direct instruction dalam pembelajaran praktik wudhu pada SDN 040 Pasawahan menghasilkan sebuah proses pembelajaran yang mampu menghidupkan suasana kelas dan mampu memberikan perubahan dalam pelaksanaan tatacara berwudhu terhadap peserta didik.